The role of vitamin D in autoimmune diseases: could sex make the difference? - Maria Luisa Dupuis; Maria Teresa Pagano; Marina Pierdominici; Elena Ortona (Biology of Sex Differences, 2021)
Abstract Over the last decades, a central role for vitamin D in immune modulation has been well established. The active form of vitamin D, i.e., 1,25-dihydroxyvitamin D, through the interaction with vitamin D receptor, exerts different activities on the innate and adaptive immune system, among which suppression of inflammation and promotion of tolerogenic responses. Vitamin D insufficiency has been linked to autoimmune disorders that commonly display significant differences between females and males due to genetic, epigenetic, hormonal, and environmental factors. Notably, a number of studies recently showed a cross-talk between vitamin D and the sex hormone estrogen. Estrogen-mediated effects on immune response may favor a Th1 profile or a Th2 profile, depending on hormone concentration. Thus, estrogen-mediated effects appear to be variable on autoimmunity depending on its concentration but also on the pathogenic mechanisms underlying the different autoimmune diseases (i.e., Th1- or Th2-mediated diseases). Notably, estrogen has been demonstrated to enhance vitamin D function favoring its accumulation, and increasing the expression of vitamin D receptor, thus resulting in a more potent anti-inflammatory response in females than males. On the other hand, vitamin D has been shown to downregulate in immune cells the expression of aromatase, which converts testosterone to estrogen, leading to a decrease in estrogen level. Overall, available data allow us to hypothesize a higher protective effect of vitamin D-based therapeutic approaches in women, at least in fertile age, than in men. Future studies are needed to expand current knowledge on the immunomodulatory role of vitamin D in a sex and gender perspective, paving the way to a more personalized therapeutic approach in autoimmune diseases.